DRAMATURGI PROSES PERSIDANGAN FERDY SAMBO DIANTARA PERSONAL BRANDING DAN VONIS HUKUMAN MATI - Tuty; Hardian, Arvin; Raharjo, Agung (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
The first trial in the premeditated murder case of Brigadier Joshua began at the South Jakarta District Court, Monday (17/10). During the initial hearing, it was revealed that the former Head of the Propam Polri division, Ferdy Sambo, had also shot the victim to kill his wife's adjutant. A dramaturgy of Ferdy's sambo between the confessions in court and the death sentence. At least the public was forced by national television stations to enjoy Fredy Sambo's dramaturgy for the last eight months, from mid-2022 to early 2023. In the process broadcast by several television stations, Ferdy Sambo displays his unique character and style to build a personal brand (personal branding) in front of the screen. glass. It is the TV One station that intensely broadcasts the trial process by displaying several statements, Ferdy Sambo's appearances and gestures during the trial process. Data analysis uses Huberman and Miles namely Data Reduction by collecting field data such as television news shows, informant interviews. The results of the study were (1) the front stage process, namely the concept on television that saw Fredy Sambo in the courtroom, the style with the concept and attributes during the trial looked more casual with plus glasses, serious, professional and calm in answering questions from the team of lawyers in answering questions about the chronology of events, until implementation of content creation of defense answers. (2) of the eight personal branding concepts applied by Ferdy Sambo perfectly in conveying facts, such as gestures and language speech he constructs positively, (3) From the eight factor concepts personal branding is formed by elaborating the front stage and back stage in dramaturgical theory, the form Ferdy Sambo's personal branding was apparently unable to create a positive impression on the judge by sentencing him to death. The recommendation from this study is for personal branding actors to apply personal branding elements not to resolve all forms of conflict without being able to prove the real facts.